Revolusi Teknologi Informasi: Adaptasi Masyarakat terhadap Perubahan di Era Digital - Endang Wiguna W; Mutiara Permana; Nur Oktaviani S; Faisal Dudayef (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The information technology revolution has brought significant changes to almost all aspects of people's lives, from communication patterns and ways of obtaining information to production and trade systems across various sectors. The development of digital technology has also driven cultural, social, and economic changes that require society to continuously adapt. This article aims to examine how society adapts to these changes through a literature review approach, examining various relevant scientific sources. The discussion focuses on digital literacy, human resource (HR) transformation, the concept of Society 5.0, the psychological impact of digital technology use, the role of public policy, and the use of technology in the economic sector. The study results indicate that the success of societal adaptation is greatly influenced by the level of digital literacy and the readiness of human resources to face increasingly rapid technological developments. Furthermore, public policies that support equal access to technology and digital education are crucial factors in this adaptation process. Equitable digital literacy and the development of adaptive and flexible human resources are key strategies for maximizing digital economic opportunities while addressing various social challenges in the era of information technology transformation.